Age, growth and food of the Burbot Lota lota in two eutrophic lakes in southeast - Leif Asbjørn Vøllestad (Fauna Norvegica)
The growth and food of the burbot Lota lota was studied in two neighbouring meso-eutrophic lakes in southeast Norway. The burbot grew slower and reached smaller theoretical maximum lengths in Lake Øgderen than in Lake Rødenes (L∞ = 40.5 cm vs 69.5 cm). The diet was also different. In Lake Øgderen the burbot ate mainly ruffe Acerina cernua, smelt Osmerus eperlanus, and Mysis relicta. In Lake Rødenes the burbot also ate large quantities of Gammaracanthus loricatus and Pailasea quadrispinosa. These two amphipods are suggested to be key food items especially for the younger burbot.